Bioaccumulation of Zn and 137Cs in Glauconomya virens (Linnaeus, 176) Upon Exposure to Sigle and Mixture of Zn or 137Cs and Salinity (Jurnal Pendidikan IPA Indonesia, 2021)
This study aims to determine the effect of concentrations and salinity of seawater on the bioaccumulation of zinc and cesium in the Glauconomya virens. Salinity conditions and contaminant concentrations in the marine environment can change due to weather and other inputs.  A biokinetic experiment was carried out using a single compartment approach that used radiotracer 65Zn and 137Cs.  The experiments conducted were biota collection, acclimatization, bioaccumulation, and elimination. Acclimatization aims for the adaptation of biota in an experimental environment. Bioaccumulation was by placing the biota in an aquarium containing seawater media spiked by  65Zn, Zn, and 137Cs radiotracer contaminants. The elimination process was the release of contaminants from the body of the biota by placing them in clean and flowing seawater. The experimental results show that the uptake and elimination of Zn and Cs were influenced by these two parameters (water concentration and salinity). The highest value of Concentration Factor (CF) for Zn was 11.14 ml.g-1 under influences its concentration of  0.7 ppm in water.  In the depuration process, Zn maintained by G virens were  39.44; 31.17; 23.62; and 23.92% after these organisms accumulate this element from seawater containing 0.1; 0.3, 0.5, and 0.7 ppm, respectively. The highest of 137Cs  under influences its concentration of 3 Bg.ml-1 reached 2.65 mL.g-1. The effect of salinity is directly proportional to the factor value of Zn and 137Cs concentration.